Computer modelling of the energies and vibrational properties of hydroxyl groups in a- and B-Mg2SiO4 - Walker, A.; Demouchy, S.; Wright, Kathleen (E.Schweizerbart'sche Velagsbuchhandlung, 2006)
The structure, formation energies and infrared (IR) active vibrational modes of hydrous defects in the iron free end members of two of the most important minerals of the Earth's mantle, a- and B-Mg2SiO4, are studied by atomic-scale computational modelling in order to identify the hydrogen incorporation mechanism observed in experiment. Two computational methods are used; calculations based on inter-atomic potentials provide information on all defect configuration in the two minerals, and a combined quantum mechanical/molecular mechanics embedded cluster method is used to validate selected results. For forsterite (B-Mg2SiO4), the results suggest that IR bands at low frequencies (wavenumbers 3000-3250 cm-1) are related to protons populating M1 vacancies. Despite the unfavourable creation of silicon vacancies, calculated medium- and high-frequency IR bands are linked to protons occupying vacant Si sites. For iron-freewadsleyite (B-Mg2SiO4) IR frequencies for hydrated cation vacancies have been calculated for the first time. The main doublet at 3360-3326 cm-1 is attributed to two OH groups located in a vacant M3 site. IR bands at higher wavenumber such as the anisotropic doublet at 3615-3580 cm-1 appear to be linked to OH in vacant Si sites. Low accuracy on the calculated frequencies does not permit a strict and rigorous assignment of each individual IR band observed in hydrous forsterite and wadsleyite. However, it does allow the identification of the most favourable site for protonation and provides a useful approximation to the corresponding IR stretching frequencies for a given hydrogen incorporation mechanisms in these nominally anhydrous silicate structures.